The pains of crimmigration imprisonment: perspectives from a norwegian all-foreign prison - Ugelvik, Thomas (The British journal of criminology, 2018)
In the second part of his article on Scandinavian exceptionalism, John Pratt identified certain developments that might undermine the exceptional status of Scandinavian prisons and penal culture. A major problem looming on the horizon, according to Pratt, was the effects of globalization on Scandinavian societies. Since then, scholars have claimed that a bifurcation is emerging in the Norwegian correctional system, with humane and inclusive punishments reserved for nationals, while a more exclusionary alternative system is being developed to respond to the perceived challenge represented by foreign nationals. The opening of Norway’s first all-foreign prison in 2013 has been seen as part of this trend. In this article, we describe three pains of imprisonment experienced by foreign national prisoners: those of (1) discrimination; (2) long-distance relationships; and (3) deportability. We argue that these are all specifically tied to the prison’s status as an all-foreign prison.